2020
DOI: 10.3390/molecules25245803
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene: Preventive Role for Type 2 Diabetes Mellitus and Obesity: A Review

Abstract: Carotenoids are vital antioxidants for plants and animals. They protect cells from oxidative events and act against the inflammatory process and carcinogenesis. Among the most abundant carotenoids in human and foods is β-carotene. This carotenoid has the highest level of provitamin A activity, as it splits into two molecules of retinol through the actions of the cytosolic enzymes: β-carotene-15,15′-monooxygenase (β-carotene-15,15′-oxygenase 1) and β-carotene-9′,10′-dioxygenase (β-carotene-9′,10′-oxygenase 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 63 publications
2
47
0
3
Order By: Relevance
“…For example, β-carotene has been reported to be negatively associated with obesity and serum triglycerides [ 8 ]. It has been reported that β-carotene and its metabolites by β-carotene-9′,10′-dioxygenase control lipid metabolism within adipocytes, inhibit adipocyte maturation transformation, and suppress cell differentiation [ 33 ]. However, further studies are needed to elucidate the mechanisms by which lutein and β-carotene affect VFA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, β-carotene has been reported to be negatively associated with obesity and serum triglycerides [ 8 ]. It has been reported that β-carotene and its metabolites by β-carotene-9′,10′-dioxygenase control lipid metabolism within adipocytes, inhibit adipocyte maturation transformation, and suppress cell differentiation [ 33 ]. However, further studies are needed to elucidate the mechanisms by which lutein and β-carotene affect VFA.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the National Health and Nutrition Examination Survey 2007–2014 found that dietary β-carotene intake was inversely associated with hypertension in US adults [ 43 ]. β-carotene has also been demonstrated to play a preventive role in type 2 diabetes [ 15 , 44 ]. β-carotene modulates blood pressure and the metabolism of blood glucose due to its antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…β-carotene is known to be highly absorbed and utilized in humans [13]. Studies have found that β-carotene acts as an antioxidant to protect against cardiovascular disease [14], type 2 Nutrients 2021, 13, 2280 2 of 12 diabetes, and obesity [15]. A recent systematic review and meta-analysis concluded that β-carotene status was inversely associated with metabolic syndrome [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques used for this purpose differ in terms of repeatability and costs associated with the necessity of using specialized equipment. Valuable reviews, published in recent years, describe problems related to (i) the mechanisms responsible for the antioxidant activity [ 17 ]; (ii) the antioxidant activity of natural extracts prepared from various plant species [ 36 ], microorganisms [ 37 ], and food ingredients [ 38 ]; and (iii) the preventive role of antioxidants in various diseases such as diabetes [ 39 ], human gut diseases [ 40 ], and cancer [ 41 ], as well as the use of natural extracts for the synthesis of nanoparticles [ 42 ].…”
Section: Introductionmentioning
confidence: 99%